Compensatory Conservation of Public Trees in India: Bridging the Science, Policy and Practice - TAMBE, SANDEEP; RAWAT, GOPAL S.; GHOSH, NILANJAN; RANJITSINH, M.K.; RAWAT, ARUN SINGH; KRISHEN, PRADIP; TAKPA, JIGMET (Indian Forester, 2022)
Abstract Public trees such as those along highways, roads, canals etc. play a vital role in making our cities livable. What is the conservation status accorded to these trees? The study revealed that the state laws are designed to protect the trees from the actions of individuals but not from state projects that are emerging as the biggest threat. We recommend the need to formulate a national law that stipulates a mitigation hierarchy of avoidance, reduction and offsetting. For offsetting, we suggest a cost-based approach and developed a formula for assessing the value of the trees. The findings of this study will be of relevance to the global south that is rapidly urbanizing to preserve its green spaces.